A Cross-sectional Study of Patients With Extrapulmonary Tuberculosis and Normal Chest Radiographs — What Characteristics Were Associated With Sputum Culture Positivity?. (6th May 2022) - Le, Victoria; Pascopella, Lisa; Westenhouse, Janice; Barry, Pennan
Abstract: Background: Recognizing pulmonary involvement in tuberculosis (TB) patients is necessary to prevent TB transmission. We describe frequency and characteristics of patients with extrapulmonary TB (EPTB), normal chest radiographs, and positive sputum culture. Methods: We analyzed data of patients ≥15 years of age with EPTB reported to the California TB registry during 2011–2017 with cultured sputum and normal chest radiographs using generalized linear modeling to estimate prevalence ratios associated with positive sputum culture. Demographic, behavioral, clinical characteristics, and testing were compared for patients with positive and negative sputum culture. Results: Of 1635 patients with EPTB and normal chest radiographs, 937 (57%) had sputum culture performed, and 127 (13%) patients had positive results for Mycobacterium tuberculosis complex. Patients with positive results were more likely to: be male, experience homelessness, use substances, have HIV, and have >1 disease site. Among 85 patients with HIV co-infection, 54% had positive culture results compared with 9.5% among 852 patients without HIV co-infection. Patients with EPTB in more than 1 site were also more likely to have a positive sputum culture. Conclusions: Culturing sputum from patients with EPTB identified pulmonary cases not detected by chest radiograph, particularly among patients with HIV or >1 disease site. Abstract : Recognizing pulmonary involvement in tuberculosis (TB) is necessary to prevent transmission. Culturing sputum from patients with extrapulmonary TB identified pulmonary cases not detected by chest radiograph, particularly among patients with human immunodeficiency virus or >1 disease site.